2005
DOI: 10.13031/2013.18141
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of an Optical Method for Modeling the Dilution of Fat Globules in Whey During Syneresis of Cheese Curd

Abstract: An optical sensor designed to measure whey fat concentration was tested on whey samples from a cheese processing plant. Whey samples were collected to determine syneresis kinetics at different times after gel cutting. Normalized spectral sidescatter intensity was measured by mean of a fiber optic spectrometer (300-1100 nm). A sidescatter waveband ratio (S 875/425) was calculated by dividing intensity at 875 by that at 425 nm. Whey fat concentrations were predicted by using the power low type equation previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The results confirmed that fat dilution in whey followed a first-order response. The light side scatter technology for determining syneresis kinetics was considered to have potential but requires additional work to improve its measurement accuracy (Castillo, Payne, Lopez, Ferrandini, & Laencina, 2005b). However, these results suggest that whey fat concentration during syneresis could be measured with an in-line fibre optic sensor (Castillo, Payne, Lopez, Ferrandini, & Laencina, 2005a), that would then allow for the predictive control of this cheese manufacturing process.…”
Section: Cheese Manufacturementioning
confidence: 99%
“…The results confirmed that fat dilution in whey followed a first-order response. The light side scatter technology for determining syneresis kinetics was considered to have potential but requires additional work to improve its measurement accuracy (Castillo, Payne, Lopez, Ferrandini, & Laencina, 2005b). However, these results suggest that whey fat concentration during syneresis could be measured with an in-line fibre optic sensor (Castillo, Payne, Lopez, Ferrandini, & Laencina, 2005a), that would then allow for the predictive control of this cheese manufacturing process.…”
Section: Cheese Manufacturementioning
confidence: 99%
“…We noted v 2 [n] the nth sample of the series. The nth sample v 1 [n] was estimated by: (3) with (4) (5) (6) . (7) (b 1 ) was a numerical approximation of relation (2).…”
Section: Appendix Amentioning
confidence: 99%
“…An interesting application of optical sensor technology has been proposed by Castillo et al [5,6]. Whey fat was considered as an internal tracer of whey expulsion during syneresis.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many papers have described the use of NIRS in food analysis, including the quality control of wheat flour of milling industry (Miralbés 2004), the chemical composition of butter (Hermida et al 2001), cocoa powder (Veselá et al 2007), and grass silage (Villamarín et al 2002), and the nutritional evaluation of cereals (Soares et al 1998) and feed for rabbits (Xiccato et al 1999(Xiccato et al , 2003. Work related to quality control of cheeses include the determination of whey fat (Castillo et al 2005), the determination of total solids and protein content in cheese curd (Sultaneh and Rohm 2007), the prediction of major components in commercial cheese (González-Martín et al 2008), and the prediction of fatty acid composition of fresh and freeze-dried cheeses (Lucas et al 2008).…”
Section: Introductionmentioning
confidence: 99%